Policy leadership in the European Commission: the regulation of EU mobile roaming charges. Issue 2 (23rd February 2017) - Cini, Michelle; Šuplata, Marián
Abstract: Political leadership in the European Commission tends to be associated with high politics and the intervention therein of the Commission President. This contribution takes a different approach by viewing policy leadership by the Commission as a form of political leadership. When the Commission finds it difficult to perform a broader political agenda-setting role, it may still be able to set and deliver new policy initiatives. The contribution considers the conditions under which successful policy leadership occurs. It identifies two types of condition – political agency and policy capacity – and argues that both, together, are important in explaining successful policy leadership. Evidence is drawn from the case of European mobile roaming.